The AMIGA enhancement of the Pierre Auger Observatory. (July 2015) - Daniel, B
Abstract: AMIGA (Auger Muon and Infill for the Ground Array) is a low energy enhancement for the Pierre Auger Observatory, designed to extend its measurements down to 10 17 eV to get new insights in the region of the spectrum where the transition between galactic and extragalactic cosmic rays occurs. The current status and preliminary results from AMIGA are presented and discussed in this work.